Una relectura de los tipos de partidos. Estrategias, vínculos, transformaciones - Raniolo, Francesco (2013)
Political parties are topics well known to women and men of the XXI century that live in both democratic and authoritarian regimes. Even though political parties originally emerged in order to represent people’s claims and to organize popular participation, today they seem to be relegated to the «Palace» or places where political power can be found. They have weak social roots, but exert a wide control of the State. This article retraces the parabola of political parties, highlighting their nature as complex organizations. Parties have to face four «organizational problems» related to: internal participation, organizational structure, mobility of resources and relations with their environment (strategic problem). Generally, parties adopt strategies to maximize their votes, presence in office and policy seeking, or their mix. These strategies usually affect the ways to face and eventually solve other organizational problems. The same historical party types will be examined through the analysis of these external and internal organizational problems.